Preparedness toward participation in disaster management: An online survey among dental practitioners in a disaster-prone region of Eastern India - Sri Priya Narayanan; Hemamalini Rath; Shilpa Mahapatra; Manoranjan Mahakur (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Dentists are often overlooked resources in the workforce for disaster management (DM). To determine the knowledge, attitudes, willingness, and self-perceived effectiveness to participate in DM among general dental practitioners (GDPs) of Eastern India. MATERIALS AND METHODS: A web-based online survey was conducted among 256 Dental Council of India registered GDPs of Cuttack district, Odisha. The 45-item survey comprised closed-ended questions on the demographic data of the participants, years of practice, previous experience in DM, and willingness to participate. Other domains assessed were the participants' objective knowledge of DM, attitude, and self-perceived effectiveness toward participation during disasters. Data were analyzed descriptively, and the Chi-square and Mann-Whitney U tests were used for statistical analysis, with a significance threshold of P < 0.05. RESULT: A total of 154 responses were analyzed, giving a response rate of 60.16%. The average age was ≤35 years, 59.1% were BDS dentists and 78.6% had less than 10 years of practice. Only 18% of them had previous experience with DM, and merely 3.2% were formerly trained; however, 95.5% of the dentists were willing to participate in DM. The mean DM knowledge and attitude scores were 16.12 (CI = 15.4-16.8) and 5.79 (5.45-6.13), respectively. Knowledge and attitude showed a significant correlation. About 56% indicated that they would be able to respond effectively to a disastrous event. Significant associations were observed between age group (P = 0.008), years of clinical practice (P = 0.001), qualification (P = 0.012), previous participation (P = 0.029), and self-perceived effectiveness. CONCLUSION: The knowledge regarding DM among respondents was at an average level. However, the majority of them were found to have a positive attitude toward participation in DM. Thus, including DM in dental curricula and drills for dental professionals might prove beneficial as almost all GDPs were showing greater self-perceived effectiveness and willingness to participate in disasters.